2018
DOI: 10.1038/s41431-017-0051-9
|View full text |Cite
|
Sign up to set email alerts
|

CXorf56, a dendritic neuronal protein, identified as a new candidate gene for X-linked intellectual disability

Abstract: Intellectual disability (ID) comprises a large group of heterogeneous disorders, often without a known molecular cause. X-linked ID accounts for 5-10% of male ID cases. We investigated a large, three-generation family with mild ID and behavior problems in five males and one female, with a segregation suggestive for X-linked inheritance. Linkage analysis mapped a disease locus to a 7.6 Mb candidate region on the X-chromosome (LOD score 3.3). Whole-genome sequencing identified a 2 bp insertion in exon 2 of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…The last XLID update published, estimated that 141 genes are associated with XLID. Since then, more genes have been associated to XLID such as CXorf56 , HS6ST2 , NAA15 , POLA1 and SLC9A7 (Figure ). However, the link of some of these genes to XLID is still questionable .…”
Section: Introductionmentioning
confidence: 99%
“…The last XLID update published, estimated that 141 genes are associated with XLID. Since then, more genes have been associated to XLID such as CXorf56 , HS6ST2 , NAA15 , POLA1 and SLC9A7 (Figure ). However, the link of some of these genes to XLID is still questionable .…”
Section: Introductionmentioning
confidence: 99%
“…In our patients, an in-frame deletion of two residues and an insertion-deletion leading to a frameshift and premature stop were identified. Both variants are located more C-terminal (exons 4 and 5) to the previously reported variant by Verkerk et al (exon 2) [5], which was shown to be subjected to NMD, with loss-of-function as the likely disease mechanism. The newly described variants are inferred to lead to LoF.…”
Section: Discussionmentioning
confidence: 68%
“…The previously reported female by Verkerk et al presented mainly with moderate ID, behavioral issues, and mild dysmorphic features. X-chromosome inactivation analysis did not show a skewed methylation pattern (54%) in the affected female, while six unaffected female carriers showed a 76-93% inactivation of the maternally inherited allele [5]. X-methylation analyses in three females from family 1 (two mildly affected and one unaffected) confirmed skewed X-inactivation in blood cells from mildly symptomatic females (97 and 83%, II-2 and II-6), while 100% skewed X-inactivation pattern of the putative carrier chromosome was observed in the asymptomatic female (I-2).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations